INCLUSION OF MEAT COMPLEMENTARY FOOD INTO INFANTS’ DIET - M. O. Revnova (Вопросы современной педиатрии, 2011)
Main questions of meat inclusion into complementary food in infants’ diet are described. Author analyzes the role of several components of meat complementary food (protein, iron) which is necessary to growing and development organism. Inclusion of meat complementary food should be combined with products favoring to better meat uptake, particularly with vegetables and cereals rich with iron.